A bird’s eye view on Muslim scholarship in Southeast Asia - Ahmad H.Osman, Rahmah; Mohd Muhedat, Khaled Ahmad (Common Ground Publishing Pty Ltd, 2009)
In this study, we will take a look at the biographies and contributions of 10 prominent scholars who played significant roles in the development and progress of the societies in the Malay Archipelago as well as the dissemination and better understanding of Islamic teachings among the people at that time. We understand that there are more than 10 great scholars of Nusantara, however to include all of them or even half of them in our study, is definitely a heavy, time and energy-consuming task and hence, we have decided to limit the number of scholars to only 10. This is not to mean that these 10 scholars make up the list of the top 10 or best scholars of Nusantara. There is no ranking intended and the reasons that we have chosen them are more based on the availability of information, the significance of their contributions as well as their influence on the people.